2008
DOI: 10.1243/09544070jauto99
|View full text |Cite
|
Sign up to set email alerts
|

Study on cycle-by-cycle variations of combustion in a natural-gas direct-injection engine

Abstract: In this paper, the cycle-by-cycle variations of a compressed-natural-gas (CNG) direct-injection (DI) engine were investigated. The results show that the CNG DI engine has a better lean burn capability, and misfire cycles and partial burn cycles exist when the engine operates at small equivalence ratio (>0.4). Meanwhile, the indicated mean effective pressure (IMEP) has a low value, and the high value of the coefficient of variation in the IMEP is presented in comparison with those operating at a high equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…To verify the combustion stability of the diesel engine operation at idle using each test fuel, the coefficient of variation (COV) for the indicated mean effective pressure was used, which is defined as [12,13,29]:…”
Section: Discussionmentioning
confidence: 99%
“…To verify the combustion stability of the diesel engine operation at idle using each test fuel, the coefficient of variation (COV) for the indicated mean effective pressure was used, which is defined as [12,13,29]:…”
Section: Discussionmentioning
confidence: 99%
“…Recently it also has been studied in homogeneous charge compression ignition (HCCI) engine processes [14], compression ignition engines [15] and also by using CFD simulations [16]. A traditional [17][18][19][20][21][22] estimator of the cycle-to-cycle variation is the Coefficient of Variation in Indicated Mean Pressure, COV IMEP . In this paper, the authors propose complementary considering the variation of the mass fraction burning rate of each individual cycle to characterize cyclic variation, as explained later (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the nature and dynamics of the CCV in order to develop effective strategies for controlling them [25,26]. Several investigators have examined the CCV in spark ignition, compression ignition, and HCCI engines [27][28][29][30][31][32][33][34][35][36][37][38]. For the conventional spark-ignition engine, the studies revealed that variations occurring mainly in the early combustion stage influenced the CCV of indicated mean effective pressure (IMEP), and any factor which can increase the burning velocity of the mixture will lead to a reduction of the CCV [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%